ON SPACE-LIKE GENERALIZED CONSTANT RATIO HYPERSUFACES IN MINKOWSKI SPACES - Akbay, Alev Kelleci; Turgay, Nurettin Cenk; Ergut, Mahmut (Inst Applied Mathematics, 2022)
In this work, we move the study of generalized constant ratio hypersurfaces started in [6] into the Minkowski space. First, we get some geometrical properties of a non-degenerated GCR hypersurface in an arbitrary dimensional Minkowski space. Then, we obtain the complete classification of space-like GCR hypersurfaces with vanishing Gauss-Kronecker curvature in the Minkowski space E-1(n). We also give some explicit examples.
Keywords: generalized constant ratio hypersurfaces; Minkowski spaces; space-like submanifolds; flat hypersurfaces